Identification of a Novel OX40L+ Dendritic Cell Subset That Selectively Expands Regulatory T cells. Issue 1 (December 2018) - Marinelarena, Alejandra; Bhattacharya, Palash; Kumar, Prabhakaran; Maker, Ajay; Prabhakar, Bellur
Abstract We have previously shown GM-CSF derived bone-marrow dendritic cells (G-BMDCs) can induce the selective expansion of Tregs through the surface-bound molecule OX40L; however, the physiological role of thisex vivo derived DC subset remained to be elucidated. We determined GM-CSF administration to mice induced the generation ofin vivo derived OX40L+ DCs, phenotypically similar toex vivo OX40L+ G-BMDCs, in the spleen, brachial lymph nodes and liver. The generation of OX40L+ DCs correlated with increased percentages of functionally suppressive Tregs in the spleen, brachial lymph nodes, and liver of GM-CSF treated mice. DCs from GM-CSF treated mice expanded Tregs in CD4+ T-cell co-cultures in an OX40L dependent manner, suggesting OX40L+ DCs may play a role in peripheral Treg homeostasis. Furthermore, comparing the transcriptome data of OX40L+ DCs to that of all immune cell types revealed OX40L+ DCs to be distinct from steady-state immune cells and, microarray analysis of OX40L+ G-BMDCs and OX40L− G-BMDCs revealed higher expression of molecules that are associated with tolerogenic phenotype and could play important roles in the function of OX40L+ DCs. These findings suggest that OX40L+ DCs may represent a unique DC subset induced under inflammatory conditions that may play an essential role in maintaining Treg homeostasis.